Audit Market Concentration and Audit Quality of Listed Industrial Firms in Nigeria - O. Oladutire; S. O. Olabisi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study examined the effect of audit market concentration on the audit quality of listed industrial firms in Nigeria. With the aim of investigating the level of influence audit fees, auditor tenure, and audit firm size would affect audit quality, the study made use of discretionary accruals for audit quality measures. The study adopted an ex-post facto research design. In addition, the corporate annual reports and websites of ten (10) sampled listed industrial firms for the period 2012-2021 were utilized as the main sources of secondary data. In testing the research hypotheses and ascertaining the significant effect of the independent variable i.e., audit market concentration (proxy by audit fees, auditor tenure, and audit firm size) and dependent variable (i.e., audit quality), the study utilized a multiple regression technique method of data analysis. The findings from the study revealed that audit fees and audit firm size have a positive relationship with audit quality. However, an auditor’s tenure has no significant impact on audit quality. The study concluded that audit market concentration and audit market size would positively influence the audit quality of listed industrial firms in Nigeria. The study, therefore, recommended that audit fees and audit firm size should be given more attention in the course of considering the attribute of audit firms and the quality of audits in Nigeria. Thus, the study, therefore, suggested that further validation should be expanded to longer periods and more samples.